Preparation and Characterization of Electrospun Gelatin Nanofibers for Use as Nonaqueous Electrolyte in Electric Double-Layer Capacitor - Ditpon Kotatha; Masaharu Hirata; Mayuko Ogino; Satoshi Uchida; Masashi Ishikawa; Tetsuya Furuike; Hiroshi Tamura (Journal of Nanotechnology)
A novel nanofibrous gel electrolyte was prepared via gelatin electrospinning for use as a nonaqueous electrolyte in electric double-layer capacitors (EDLCs). An electrospinning technique with a 25 wt% gelatin solution was applied to produce gelatin electrospun (GES) nanofiber electrolytes. Structural analysis of the GES products showed a clearly nanofibrous structure with fiber diameters in the 306.2–428.4 nm range and exhibiting high thermal stability, high tensile strength, and a stable form of nanofibrous structure after immersion in 1-ethyl-3-methylimidazolium tetrafluoroborate (EMImBF4). After testing over a range of spinning times, GES electrolytes that were produced at 25 min (GES-25) had a suitable thickness for the assembly of EDLC with the optimized tensile properties and were used to fabricate EDLC test cells with EMImBF4. These test cells were compared to those with pure EMImBF4 and a separator as an electrolyte. The electrochemical properties of the test cells were characterized by charge-discharge testing, discharge capacitance, and alternative current (AC) impedance measurements. AC impedance measurements showed that the test cell with the GES-25/EMImBF4 gel electrolyte showed slightly poorer contact with the electrode when compared to that with pure EMImBF4, whereas exhibited comparable IR drop and discharge capacitance (calculated capacitance retention was 56.6%). The results demonstrated that this novel gel electrolyte can be used as a nonaqueous electrolyte in order to improve the safety in EDLCs.